MENINGKATKAN HASIL BELAJAR FIQIH MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE PADA SISWA KELAS VI - Soepratman, Soepratman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This Classroom Action Research (CAR) aims to improve the activity and learning outcomes of Fiqh of grade VI students of MIS Tuhfatul Athfal Sungai Raya through the application of the picture and picture type cooperative learning model. The study was conducted in two cycles, involving 24 students. Learning activity data were collected through observation, while learning outcome data were obtained through tests. The results of the study showed a significant increase in both aspects. Students' learning activities increased from the category of